SISTEM INFORMASI DATA PENJUALAN PADA PT. TRIUM PUTRA PRIMA: PT. Trium Putra Prima, Information Systems, Sales, Visual Basic 6.0 - -, Elzas (LP2M Universitas Nurdin Hamzah, 2018)
PT. Trium Putra Prima is a company engaged in the retail, especially for the Matahari Department Store. PT. Trium Putra Prima in cooperation with Matahari Departement Store by supplying Dr. products. Kevin to Matahari Departement Store, for its own data processing at Matahari Departement Store. PT. Trium Putra Prima still use manual method which where the data must be processed in the form of inputting goods, store, data of incoming goods, sales and report also still use manual method so that data obtained sometimes not accurate with existing data. Based on the above conclusions then need to be designed in order to facilitate the process of data processing. For that needed a system that will serve as a study entitled